Potensi Ekonomi Pemanfaatan Dan Pengelolaan Sekam Padi Sebagai Bioenergi: Studi Kasus Agro-Energi Kabupaten Cianjur: Economic Potential and Management of Rice Husks Utilization as Agro-Energy in Cianjur Regency - Panca Sandika; Akhmad Fauzi; Meilanie Buitenzorgy (IPB University, 2026)
Indonesia faces dual challenges in energy security and agricultural waste management. Rice husk offers significant bioenergy potential, yet its utilization is constrained by economic, social, and policy uncertainties. This study aims to analyze the economic potential of utilizing rice husks as bioenergy, analyze stakeholder perspectives, positions, and power regarding the potential use of rice husk bioenergy to map potential conflicts and align strategies. and estimate the probability of future policy scenarios regarding the implementation of rice husk use as agricultural bioenergy in Cianjur Regency to formulate priority recommendations. A three-stage integrated framework of research method was employed: Extended Cost-Benefit Analysis (eCBA), Stakeholder Analysis (MACTOR), and Probabilistic Scenario Planning (SMIC-PROB). The eCBA results indicate quite high such as feasible in economics, with a Net Present Value (NPV) of IDR 965,2 billion and a Benefit-Cost Ratio of 2,04, driven by energy substitution and the circular value of ash fertilizer. MACTOR analysis identifies a strong coalition between the government and rice millers but highlights friction with investment agencies regarding licensing. Furthermore, SMIC-PROB analysis reveals that